The Critical Edition of the Medieval Waldensian Sermons. - GIRAUDO, ANDREA (Medieval Sermon Studies, 2015)
Early Waldensian literature is an outstanding source for the study of the Waldensian movement, as it is a rare direct testimony of a dissident medieval religious movement. One of the most important genres of that literature is represented by the as yet unpublished collection of about two hundred sermons which is one of the main sources for the reconstruction of Waldensian preaching. The critical edition of this important corpus is the aim of a research group led by Luciana Borghi Cedrini (Professor of Romance Philology at the University of Turin). Established at the beginning of the millennium by the publishing house Claudiana in Turin, together with the Waldensian Studies Society and the Waldensian Church, the project is expected to be active at least until 2018 and it is officially supported by the Waldensian Faculty of Theology of Rome.